LAMP CONTROL SYSTEM THROUGH ANDROID AND WIFI BASED ON ARDUINO MICROCONTROLLER - Ricky Ramadhan Harahap; Mahardika Abdi Prawira Tanjung; Barany Fachri (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2020)
Abstract: The rapid development of digital technology has also contributed to the development of computer technology. Nowadays, many electrical devices work integrated with computer systems. This of course will greatly help human work in operating these electrical devices. One of the research that is currently being developed is about Smart Home. Smart Home has several benefits such as providing better comfort, more guaranteed safety and security, and sav-ing electricity use. By implementing Smart Home devices in homes or offices, electrical devices will be able to work automatically according to user needs. Users can also monitor and control electrical devices in the house remotely through a communication channel such as through the internet network, Wi-Fi or Bluetooth. The special properties of a microcontroller, which are small in size, save electrical power and flexibility, make the microcontroller very suitable for use as a data recorder/recorder in applications that do not require the presence of an operator.            Keywords: Arduino-Uno; ESP8266; IOT; Relay; Wifi  Abstrak: Perkembangan teknologi digital yang pesat juga turut berkontribusi pada perkembangan teknologi komputer. Saat ini banyak perangkat listrik yang bekerja terintegrasi dengan sistem komputer. Hal ini tentunya akan sangat membantu pekerjaan manusia dalam mengoperasikan perangkat listrik tersebut. Salah satu penelitian yang sedang dikembangkan adalah tentang Smart Home. Smart Home memiliki beberapa keunggulan seperti memberikan kenyamanan yang lebih baik, keamanan dan keselamatan yang lebih terjamin, serta penghematan penggunaan listrik. Dengan mengimplementasikan perangkat Smart Home di rumah atau kantor, perangkat listrik akan dapat bekerja secara otomatis sesuai kebutuhan pengguna. Pengguna juga dapat memantau dan mengontrol perangkat listrik di rumah dari jarak jauh melalui saluran komunikasi seperti melalui jaringan internet, Wi-Fi atau bluetooth. Sifat khusus dari mikrokontroler yaitu ukurannya yang kecil, hemat daya dan kelenturan listrik, menjadikan mikrokontroler sangat cocok digunakan sebagai rekorder / perekam data pada aplikasi yang tidak membutuhkan kehadiran operator. Kata kunci: Arduino-Uno; ESP8266; IOT; Relay; Wifi